2022
DOI: 10.1002/pds.5553
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multivariate prediction model to identify individual case safety reports which require clinical review

Abstract: Background The number of Individual Case Safety Reports (ICSRs) in pharmacovigilance databases are rapidly increasing world‐wide. The majority of ICSRs at the Netherlands Pharmacovigilance Centre Lareb is reviewed manually to identify potential signal triggering reports (PSTR) or ICSRs which need further clinical assessment for other reasons. Objectives To develop a prediction model to identify ICSRs that require clinical review, including PSTRs. Secondly, to identify the most important features of these repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Current model with NLP performed better than our previously developed model that had an AUC of 0.75 (95% CI: 0.73-0.77). In addition, upon visual inspection of the precision and recall plot it was found that the current model also outperformed the previous model which was only based on structured fields (non-NLP features) (Gosselt et al, 2022). From the feature importance plot it can be seen that the feature 'info_length' seemed of high importance to distinguish case reports from non-case reports.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Current model with NLP performed better than our previously developed model that had an AUC of 0.75 (95% CI: 0.73-0.77). In addition, upon visual inspection of the precision and recall plot it was found that the current model also outperformed the previous model which was only based on structured fields (non-NLP features) (Gosselt et al, 2022). From the feature importance plot it can be seen that the feature 'info_length' seemed of high importance to distinguish case reports from non-case reports.…”
Section: Discussionmentioning
confidence: 73%
“…Most important features in this prediction model were: "absence of ADR in the Summary of product characteristics," "ADR reported as serious," "ADR labelled as an important medical event," "ADR reported by physician" and "positive rechallenge." An AUC of 0.75 (0.73-0.77) was obtained, which can be seen as moderate model performance (Gosselt et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, systems ought to avoid over-reliance on automated standalone software programs as they could generate false signals. Instead, holistic methods which include manual review alongside automated processes should be preferred 33 34. The objective of this scoping review is to provide a comprehensive overview of duplication in pharmacovigilance databases on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited industry-wide standards that apply ML technologies in PV. Nonetheless, the number of ICSRs in PV databases are increasing, and given that individual case review is time-consuming, new approaches should be explored to help prioritize which reports require further evaluation by safety teams [ 4 ]. A previously published article revealed that ML algorithms have better accuracy in detecting new signals than traditional disproportionality analysis methods, which typically encounter some issues, such as background noise and the possibility of generating false-positive results [ 5 ].…”
Section: Introductionmentioning
confidence: 99%